Playing with Recognizers: A Call for an Extensible Editor - DAVIS, Richard C. (Institutional Knowledge at Singapore Management University, 2010)
The sketch recognition interface community has not produced a -killer‖ application, because access to sketch recognition technology has been too restricted. If recognition technologies were more freely available for experimentation, powerful new applications would evolve. This paper proposes a rough architecture for an extensible graphical editor that facilitates collaboration between recognition technology developers, user interface designers, and early adopters of sketch recognition interfaces. Only by serving all three communities will we reach the critical mass necessary for killer applications to emerge.